2014
DOI: 10.1183/09031936.00126814
|View full text |Cite
|
Sign up to set email alerts
|

INSTEAD: a randomised switch trial of indacaterolversussalmeterol/fluticasone in moderate COPD

Abstract: The Indacaterol: Switching Non-exacerbating Patients with Moderate COPD From Salmeterol/Fluticasone to Indacaterol (INSTEAD) study investigated the effect of switching patients at low risk of chronic obstructive pulmonary disease (COPD) exacerbations from salmeterol/fluticasone (SFC; inhaled corticosteroid (ICS) regimen) to indacaterol monotherapy (non-ICS regimen).This 26-week, double-blind, double-dummy, parallel-group, phase IV study, randomised 581 patients with moderate COPD to indacaterol 150 mg once dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
118
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(129 citation statements)
references
References 20 publications
2
118
1
8
Order By: Relevance
“…The crucial Indacaterol: Switching Non-exacerbating Patients with Moderate COPD From Salmeterol/ Fluticasone to Indacaterol (INSTEAD) trial, which enrolled COPD patients with moderate airflow limitation and without a history of exacerbations in the previous year, but on treatment with ICS/LABA combination therapy for ≥3 months, documented that these patients can be switched from ICS/LABA to indacaterol 150 μg with no efficacy loss [27].…”
Section: обзорыmentioning
confidence: 99%
“…The crucial Indacaterol: Switching Non-exacerbating Patients with Moderate COPD From Salmeterol/ Fluticasone to Indacaterol (INSTEAD) trial, which enrolled COPD patients with moderate airflow limitation and without a history of exacerbations in the previous year, but on treatment with ICS/LABA combination therapy for ≥3 months, documented that these patients can be switched from ICS/LABA to indacaterol 150 μg with no efficacy loss [27].…”
Section: обзорыmentioning
confidence: 99%
“…The recently developed once-daily, very long-acting LABA (indacaterol, vilanterol, olodaterol and others [62][63][64][65][66]) potentially offer better bronchodilation patterns relevant to treating severe asthma with persistent airflow obstruction. Whether these drugs will also synergistically improve asthma control and reduce exacerbation rates is unknown at present.…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…Although ever since there have been countless review papers, workshops and conferences about ''who needs ICS in COPD'', it appeared that the overuse of ICS in COPD was indeed a hard habit to break. Even when well-designed clinical trials confirmed the effectiveness of non-ICS containing combinations for COPD exacerbation prevention [6], and the feasibility of weaning off ICS in subjects with a questionable indication for this type of drug [7,8], change was reluctant and slow. Why were doctors so persistent with their prescription habits?…”
mentioning
confidence: 99%
“…Indeed, I got it wrong: the drug industry (as well as clinical researchers and expert committees) has spent (wasted?) over 20 years with the question of searching for often marginal differences in outcomes with ''optimal'' treatment regimes comparing one, two or three single or combined (pharmacologically old) components, often following their canonical imperatives of ''maximized'' bronchodilation versus ICS-containing combos: LAMA versus ICS/LABA [10], ICS/LABA versus LABA [11], LABA/LAMA versus LAMA [12,13], LABA/LAMA versus ICS/LABA [6], plus a number of studies circling around the question if it was possible to withdraw ICS safely or not [7,8,14]. Tellingly, the only study that ignored the ''one-or-another'' agenda and looked at the effects of combining all three (ICS/LABA plus LAMA) compounds together (the Canadian OPTIMA trial) [15], mimicking usual practice of clinicians, particular in more severe forms of COPD, was non-industry sponsored.…”
mentioning
confidence: 99%